Learning Strategy Using Picture Methods To Improve Students’ Speaking Ability - Pipit Sevianto (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The objectives in this study are to find out: 1) The image method has an effect on learning English for students in Muhammadiyah Junior High Schools. 2) Speaking ability in learning English in the eyes of Muhammadiyah Senior High School Students 25. 3) How much influence does the drawing method have on speaking skills in learning English in the eyes of Muhammadiyah Senior High School Students 25. This study was designed using a descriptive method with a quantitative approach. The population in this study were 22 Muhammadiyah Junior High School Students, totaling 120 of the 4 classes taken from Class XI. The sample size using the Slovin technique. In the research I did, I used 54 respondents, namely 25 Muhammadiyah high school students. The results of this study are as follows: 1) The picture method for learning English for students at Muhammadiyah Senior High School 25. If you look at the questionnaire for the Picture Method (X) variable, it can be seen from the highest respondent's answer to the answer "Disagree" which is as much as 20.06% so it can be concluded that the Picture Method in Muhammadiyah 25 Senior High School is not good. 2) The speaking ability of students' English learning at Muhammadiyah Senior High School 25. If you look at the questionnaire, the Speaking Ability (Y) variable can be seen from the highest respondent's answer to the answer "Disagree" which is as much as 24.07% so it can be concluded that the Speaking Ability in School Muhammadiyah 25 is not good. 3) There is an effect of the picture method on speaking ability in learning English in students at Muhammadiyah 25 Senior High School, it is proven that the tcount value for Picture Method (X) is 11.850, while the ttable value for N = 54 is 1.673. So tcount > ttable or 11.850 > 1.673, because H0 is rejected and Ha is accepted, it can be stated that Picture Method (X) has a significant effect on Speaking Ability (Y) at Muhammadiyah 25 Senior High School. Meanwhile, it is proven that the R Square value is 0.730. This shows that 73% of Picture Method (X) affects Speaking Ability (Y), and while the difference of 27% is influenced by other variables not examined in this research study.